Development of ssRNA for therapeutic gene knock-down - Powalowska, Paulina Klaudyna (2017)
Work presented in this thesis shows how chemical modifications of ssRNAs can increase their nuclease resistance, resulting in potent gene inhibition. The first part of thesis describes how a range of chemical modifications were introduced into the ssRNAs to test their effect on oligonucleotide stability and ability to inhibit gene expression. The ssRNAs were tested in a cancer cell line that stably expresses firefly luciferase. This work demonstrates that DNA nucleotides can be incorporated into ssRNA sequences without loss of potency in the RNAi mechanism. By using additional chemical modifications (2’-OMe and 2’-F) further improvement of ssRNA stability and a significant inhibition of firefly luciferase activity, reaching 91%, was achieved. Moreover, we show that the level of inhibition can be improved when the DNA dinucleotide linked by the (E)-vinylphosphonate is used as a protection of the 5’-end of the ASO (95% KD). The use of ssRNAs rather than dsRNAs is beneficial, since the possibility of off-target effects caused by the remaining sense strand is eliminated and the cost of production of such a medicine is reduced. The second part of this thesis focuses on development of an experimental system that will allow detection of the inhibition of a disease relevant target. Several approaches were used in order to detect KD of the target by the unmodified dsRNAs. First a western blotting technique was employed for detection. Although different ASOs and concentrations were used no KD was observed. More attempts were taken in order to generate target KD, but unfortunately they were unsuccessful so far.